Desafios da educação inclusiva: - ALMEIDA, Ludemilla Santos. (Universidade Federal do Tocantins, 2024)
Inclusive Education has been frequently discussed, the struggle for social inclusion and the achievement of equal conditions for access and permanence in school has gained space and been the subject of discussions in basic documents of education, such as the BNCC. Teacher training influences the training of professionals who will work with people with disabilities. Thus, the objective of this work is to identify and analyze the teaching challenges faced by teachers within the scope of Inclusive Education, as well as to analyze whether the State School of Muricilândia and the State School Machado de Assis have adequate structures to accommodate students with disabilities. Qualitative research and observational research were used as study methodology, followed by bibliographic surveys. This study showed us that one of the biggest challenges for schools in the inclusion process is the lack of financial investment from the government directed to AEE, and that the difficulty that teachers have in teaching an inclusive class is a reflection of the lack of disciplines in the undergraduate course focused on Inclusive Education.